The influence of shallow elastic heterogeneities on the subsidence bowl resulting from deep reservoir depletion - González Acosta, J. L.; Candela, Thibault; Pluymaekers, Maarten; Zhai, Guang; Koster, Kay; Fokker, Peter A.; Aben, Franciscus (Frontiers in Earth Science, 2026)
Subsidence due to gas extraction poses significant risks to infrastructure, as even moderate vertical displacements can cause structural damage. Existing models typically predict smooth, broad subsidence bowls, but observational data reveals short-wavelength fluctuations superimposed on this pattern, which are crucial for assessing the potential risk of damage. Current models overlook these variations, leading to an incomplete understanding of subsidence-induced hazards. This research aims to assess the role of shallow elastic heterogeneities in explaining these short-wavelength subsidence fluctuations. We combined InSAR observations with finite element subsidence modelling in the Groningen gas field to analyze the effects of shallow geological structure and elastic moduli variations. Our results show that small-scale elastic heterogeneities cause local displacement changes ranging from 1% to 9%, consistent with InSAR observations, while horizontal strains can vary significantly by 30%–200%. These findings highlight the importance of accounting for short-wavelength fluctuations in subsidence models, as they have direct implications for risk assessment and predicting building damage due to gas extraction.